Evaluasi Website Ngalup.Co Working Space Menggunakan User Experience Questionnaire (UEQ) Dan Focus Group Discussion (FGD) Untuk Meningkatkan User Experience - Fitra Endi Auliansyah; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ngalup.co Working Space is a company located in City of Malang that provides working space compilation service, event hall, and meeting room. Website of Ngalup.co Working Space provides information about company profile, services, event held, partnership, pricing, testimony, and blog. For a website that gives information about company and its services must have a good user interface design to improve user experience of website's users. User experience of Ngalup.co Working Space's website assessed by User Experience Questionnaire (UEQ) using six scales: Attrativeness, Perspicuity, Efficiency, Dependabilty, Stimulation, and Novelty. The aims of the study were to find out quality level of user experience and redesign website of Ngalup.co Working Space to improve user experience by using User Experience Questionnaire (UEQ) and Focus Group Discussion (FGD). Evaluating a website for a company is an important thing to meet user needs. The result of UEQ were need to imrpoves on all scale of UEQ especially at perspicuit and dependabilty scale that user understanding of given information. Redesign user interface website of Ngalup.co Working Space improve its user experience at all scales.